Exploring the spatiotemporal changes and influencing factors of urban resilience based on Scale-Density-Morphology—A case study of the Chengdu-Deyang-Mianyang Economic Belt, China - He, Wei; Zheng, ShiWei; Zhao, XiaoQuan (Frontiers in Environmental Science, 2023)
It is of great significance to carry out research on the evolution of urban resilience and the detection of influencing factors to promote urban safety management and guide urban planning. This paper constructs urban resilience evaluation indicators based on Scale-Density-Morphology, adopts the “polyhedron method” to evaluate the urban resilience of the Chengdu-Deyang-Mianyang Economic Belt from 2010 to 2020, analyzes the temporal and spatial changes in urban resilience, and explores the impact of natural, social, economic and other factors on urban resilience, to provide a basis for regional sustainable development. The results show that 1) The overall level of urban resilience is not high, showing a clear downward trend and imbalance. Urban resilience decreased from 0.296 in 2010 to 0.213 in 2020. The proportion of districts and counties with high urban resilience is relatively small and continues to decline. The differences in urban resilience in the region are significant and gradually increasing, and there is an obvious imbalance in urban resilience. 2) Urban resilience presents the spatial distribution characteristics of continuous expansion of low-resilience and lower-resilience urban, and shrinkage of the distribution of high-resilience and higher-resilience urban. The types of evolution are mainly manifested as rapid decline and fluctuation decline. 3) The influencing factors affecting the spatial differentiation of urban resilience are different. Ecological factors represented by per capita ecological land area have gradually become the primary factor. The influence of factor interactions is greater than that of individual factors, including both non-linear enhancement and two-factor enhancement.